Synopsis: Household perception and demand for better protection of land rights in Ethiopia - Ghebru, Hosaena; Koru, Bethlehem; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2016)
This study assesses factors that explain households’ perceived land tenure insecurity and the demand for new formalization of land rights in Ethiopia. We use data from the 2013 Agricultural Growth Program survey of 7,500 households from high agricultural potential areas of Ethiopia. The results from a descriptive analysis and a logistic estimation reveal that demand for further land demarcation is positively associated with higher perception by households of tenure insecurity. Moreover, disaggregated results indicate that ownership and boundary-related disputes characterize periurban locations and economically vibrant communities, whereas perceived risk of government expropriation of land is mainly manifested in rural communities and areas where administrative land redistribution is a recent practice.